Advances in Breast Cancer – Looking Back over the Year - Lüftner, D.; Lux, M. P.; Maass, N.; Schütz, F.; Schwidde, I.; Fasching, P. A.; Fehm, T.; Janni, W.; Kümmel, S.; Kolberg, H.-C. (Geburtshilfe und Frauenheilkunde, 2012)
Treatment options as well as the characteristics for therapeutic decisions in patients with primary and advanced breast cancer are increasing in number and variety. New targeted therapies in combination with established chemotherapy schemes are broadening the spectrum, yet not every new, promising combination achieves a better result. New data from the field of pharmacogenomics point to prognostic and predictive factors that take not only the properties of the tumour but also the genetic disposition of the patient into consideration. Current therapeutic decision-making is thus based on a combination of classical clinical and modern molecular biomarkers. Health-economic concerns are also being taken into consideration more frequently, meaning political decisions may also become a factor. This review presents the trends over the past year.
Keywords: breast cancer therapy; molecular biomarkers; targeted therapy; trastuzumab; T-DM1; everolimus